Subverting masculine ideology and monstrous power exertion in Doris Lessing‟s The Cleft - Lalbakhsh, Pedram (Pusat Pengajian Bahasa dan Linguistik, FSSK, UKM, 2014)
Women’s oppression and subjugation reflected in literature has always been a controversial issue for writers and critics and Lessing is a novelist whose long career of writing demonstrates her preoccupation with related issues. The present paper approaches Doris Lessing’s novel, The Cleft, from a socialist feminist point of view to foreground Lessing’s understanding of women in both past and present societies in which women are subjugated and oppressed by capitalist and patriarchal systems and ideologies. The author of this paper argues that characterising exploitative and dominating male characters Lessing tries to introduce them as naive and unsophisticated invaders who seem pathetic and inhumane simultaneously. She identifies an intellectual gap between males and females that can justify all the problems and miseries of female race until the twentieth century and afterward. Thus, as the author understands it, Lessing’s novel is an attempt to subvert such longestablished masculine ideology and defy the monstrous power exertion that has had women as its most important target. As Lessing shows in her novel, men’s use of a fake history and male-defined ideology has led to women’s domination and inferiority. However, she demonstrates that women’s unique intellectual power can be their weapon in fighting against patriarchy and forceful power exertion, paving the way for women to achieve their true essence. The findings of this study demonstrate that The Cleft is Lessing’s invitation to refresh women’s historical consciousness, to understand and believe that most personal problems and suffering have their equivalent in others’ lives, even in the lives of the ancestral mothers a long time before history begins.